A Francisella mutant in lipid A carbohydrate modification elicits protective immunity. - Duangjit Kanistanon; Adeline M Hajjar; Mark R Pelletier; Larry A Gallagher; Thomas Kalhorn; Scott A Shaffer; David R Goodlett; Laurence Rohmer; Mitchell J Brittnacher; Shawn J Skerrett; Robert K Ernst (PLoS Pathogens, 2008)
Francisella tularensis (Ft) is a highly infectious gram-negative bacterium and the causative agent of the human disease tularemia. Ft is designated a class A select agent by the Centers for Disease Control and Prevention. Human clinical isolates of Ft produce lipid A of similar structure to Ft subspecies novicida (Fn), a pathogen of mice. We identified three enzymes required for Fn lipid A carbohydrate modifications, specifically the presence of mannose (flmF1), galactosamine (flmF2), or both carbohydrates (flmK). Mutants lacking either galactosamine (flmF2) or galactosamine/mannose (flmK) addition to their lipid A were attenuated in mice by both pulmonary and subcutaneous routes of infection. In addition, aerosolization of the mutants (flmF2 and flmK) provided protection against challenge with wild-type (WT) Fn, whereas subcutaneous administration of only the flmK mutant provided protection from challenge with WT Fn. Furthermore, infection of an alveolar macrophage cell line by the flmK mutant induced higher levels of tumor necrosis factor-alpha (TNF-alpha) and macrophage inhibitory protein-2 (MIP-2) when compared to infection with WT Fn. Bone marrow-derived macrophages (BMMø) from Toll-like receptor 4 (TLR4) and TLR2/4 knockout mice infected with the flmK mutant also produced significantly higher amounts of interleukin-6 (IL-6) and MIP-2 than BMMø infected with WT Fn. However, production of IL-6 and MIP-2 was undetectable in BMMø from MyD88(-/-) mice infected with either strain. MyD88(-/-) mice were also susceptible to flmK mutant infection. We hypothesize that the ability of the flmK mutant to activate pro-inflammatory cytokine/chemokine production and innate immune responses mediated by the MyD88 signaling pathway may be responsible for its attenuation, leading to the induction of protective immunity by this mutant.